SOSIALISASI KEBIJAKAN KAWASAN TANPA ROKOK DI RSUD LUBUK PAKAM DELI SERDANG - Balqis Wasliati; Ika Nur Saputri; Delita Br Panjaitan; Raisha Octavariny; Christina Octavia (JURNAL PENGMAS KESTRA (JPK), 2021)
Non-Smoking Area (KTR) is a policy made by the Ministry of Health to prevent and control the health impacts caused by smoking. Control of health impacts does not only apply to active smokers, but also passive smokers and the surrounding environment exposed to cigarette smoke. The implementation method with the socialization method is an understanding of the condition of smokers in Indonesia and about KTR. In addition, it was conducted with a question and answer session and interviews with health workers and visitors related to cigarettes and KTR. The implementation of this activity is divided into three stages, namely, planning, implementation and evaluation. All health workers and the public understand the dangers of smoking but still carry out smoking activities on the grounds of addiction to cigarettes. KTR socialization provided an understanding that Deli Serdang Regional Hospital had regulations to implement and support KTR issued by the government through the Ministry of Health.